Pembuatan Keputusan Seorang Pemimpin dalam Menetapkan Progam Kerja Organisasi LDK Al-Izzah Uinsu - Lydia Amelia; Ahmad Ardhi Mauluddin (Journal on Education, 2023)
The role of the leader is very large in making decisions and taking responsibility for the results. The decision reflects the character of a leader. Decision making is very important for organizational activities is also a key leadership or core leadership. Leaders must be able to make the right decisions in various situations, by choosing the best among a number of alternative decisions they face and carefully considering them. Leaders act as individuals in the community who have authority in making decisions to achieve organizational goals. This article aims to explain the topic of making a leader's decision in determining the work program of the LDK AL-Izzah UINSU organization. This research was conducted using a qualitative-descriptive method. The results of the study show that the decisions that must be made by the leaders depend on the problems faced and alternative solutions to the problems through various approaches that can be taken by each leader as well as their abilities and skills to solve problems and make decisions, by using their conscience which is adjusted to the interests of the stakeholders. members who are in the organization concerned, in order to achieve the goals that have been determined/predetermined.In order to carry out the results of the decisions that have been determined by the leadership, the person concerned must be able to predict what the opinions, attitudes and actions of his subordinates will be like whether they are positive or negative. Try to keep subordinates' views on decisions taken by leaders always positive, so that the decisions they make run smoothly, effectively and efficiently. Organizational life will last a long time, if its members have strong motivation to unite individual goals in accordance with group and organizational goals. Organizational dynamics and organizational environment are factors that should be taken into account by every leader, so that the organization becomes effective.